Walka Wschodu i Zachodu w literaturze greckiej od Herodota do Prokopiusza z Gazy - Polański, Tomasz (Vox Patrum, 2003)
Herodotus presented the conflicts between Europe and Asia on both the mythological and historical level and made them one of the main structural and ideological components of his work. The idea of war against the Achaemenids interpreted as central to the Greek historical destiny returned time and again in the Greek letters, always blended with the symptomatic feeling of superiority and simplified standard view of the Orientals. (Euripides, Xenophon of Athens, Plato, Isocrates). The efforts to unite the Greeks and Macedonians with the Orientals which were undertaken by Alexander the Great, found little understanding among the Greeks (Plutarch). His myth as a conqueror of Asia became an ideological trap of the Hellenic as well as Roman historical thinking (Cassius Dio). Renewed and unsuccessful efforts to follow Aiexander’s steps brought interesting literary testimonies shaped by collective experiences of the insuperable climate, the fear of the epidemics, and confrontation with cunning, cruel and elusive adversaries (Plutarch, Procopius of Caesarea). The Greek literary testimonies had their alter ego in the Eastern prophetic writings, which expressed hostility towards the Greeks and Romans and predicted a final victory for the East over the West (Oracula Sibyllina, The Oracle of the Potter, The Oracle of Hystaspes). In the Wars of Procopius of Caesarea a pessimistic, purely militarist view came to the surface. It said that the loyalty of the Orientals could be secured only through the use of military power. In that period we also observe a factor of religious inspiration in the war propaganda on both sides (Procopius of Caesarea, Georgios Pisides).